Validitas Metode Konvensional Modifikasi Terhadap Metode Konvensional Dan ChromidTM Esbl Untuk Deteksi Bakteri-bakteri Penghasil Extended-spectrum Beta-lactamases - Maya Savira (Jurnal Ilmu Kedokteran, 2014)
Extended spectrum beta lactamases (ESBL) enzymes producing microorganisms are a major problem in increasingof betalactamases antibiotics resistance include cephalosporins. These enzymes are produced by gram negativesbacilli especially a variety of Enterobacteriaceae, however the most common ESBL producing microorganisms areKlebsiella spp and Escherichia coli. Detection and identification of gram negatives bacilli producing ESBL arechallenging for clinical microbiology laboratory to determine the best method to get the optimal results. The objectiveof this study was to determine the sensitivity and specificity of conventional method modification using MacConkeyadded with cefpodoxim disc 10 μg, 2 mg/l to conventional method and ChromIDTM ESBL. The method of this studywas an observasional analytical study using cross sectional design on 200 isolates, which were Escherichia coli,Klebsiella spp, Salmonella typhi, Proteus mirabilis, Pseudomonas aeruginosa, Serratia spp, and Enterobacter spp.The sensitivity of conventional method modification was 93,8%, conventional method was 68,8% and ChromIDTMESBL method was 100%. The spesificity of conventional method modification was 98,7%, conventional method was11,2% and ChromIDTM ESBL method was 100%. The sensitivity of conventional method modification was higherthan conventional method and as good as ChromIDTM ESBL for detecting ESBL producing bacterias.